Biosynthesis, regulation, and engineering of natural products from Lysobacter. Issue 4 (24th January 2022) - Yue, Huan; Miller, Amanda Lynn; Khetrapal, Vimmy; Jayaseker, Vishakha; Wright, Stephen; Du, Liangcheng
Abstract : This review summarizes progress in Lysobacter natural product research over the past 10 years, including identification, mechanisms for biosynthesis and regulation, and metabolic engineering. Abstract : Covering: up to August 2021 Lysobacter is a genus of Gram-negative bacteria that was classified in 1987. Several Lysobacter species are emerging as new biocontrol agents for crop protection in agriculture. Lysobacter are prolific producers of new bioactive natural products that are largely underexplored. So far, several classes of structurally interesting and biologically active natural products have been isolated from Lysobacter . This article reviews the progress in Lysobacter natural product research over the past ten years, including molecular mechanisms for biosynthesis, regulation and mode of action, genome mining of cryptic biosynthetic gene clusters, and metabolic engineering using synthetic biology tools.